Problem Solving untuk Meningkatkan Subjective Well-Being Hubungan Pernikahan Domisili Jarak Jauh - Dedy Kurniady; Yeni Karneli; Netrawati (Jurnal Ilmu Pendidikan dan Sosial, 2023)
This long distance marriage describes a physically separated situation where one partner has to settle in another place with certain reasons and goals such as job demands, education and others. The obstacles that can occur during this long-distance domicile marriage relationship are as follows, the couple does not feel happy, negative moods and emotions, less time together, family roles have not gone well even in fatal cases such as divorce. This study aims to improve subjective well-being for couples undergoing long-distance marriage relationships with a problem solving approach. The research design was carried out using a literature study related to problem solving approaches to increase subjective well-being for couples who are in long-distance marriage relationships. The results of this study indicate that problem solving is an effective alternative approach in increasing subjective well-being in long distance marriage.